Association of Resistin & Interleukin 6 in Ischemic Heart Disease and Diabetic Patients - Faisal Yaseen (ziauddin University, 2024)
Background: Honey is used extensively in south East Asia, Middle and Far Eastern countries as a sweetener as well as medication for its anti-bacterial, anti-fungal, and anti-viral properties with no risk of resistance or side effects. Recent studies suggest that honey can modulate tumor growth by reducing cell proliferation and increasing apoptosis susceptibility. Objective: To measure the serum levels of resistin and interleukin 6 levels in single, two vessel and three vessel disease on angiography in ischemic heart disease patients with diabetes and without diabetes. To determine an association between the biomarkers(resistin, IL-6 levels) and cardiovascular disease. Methods: A comparative cross sectional study was designed in which samples of 147 subjects were selected. Age was in range of 40 to 70 years. Subjects were divided into two groups of 38 diabetics with complication of ischemic heart disease and 38 non diabetic with ischemic heart disease. Plasma glucose was measured using the Glucose oxidase method. Resistin and interleukin-6 were determined by ELISA. Extent of vessel disease was determined by standard angiography method. Results: The total subjects included in the study were 76.Angiographic findings of 76 patients with IHD revealed that, 19 (25%) had single vessel disease (SVD), 16 (21.05%) had two vessels disease (2VD) and 41 (53.95%) had three vessels disease (3VD). Group of 38 non diabetic patients with IHD, 8 (21.1%) had SVD, 7 (18.4%) had 2VD and 23 (60.5%) had 3VD.Among 38 patients of IHD with DM, 11 (28.9%) had SVD, 9 (23.7%) had 2VD and 18 (47.4%) had 3 VD. Positive correlations of Interleukin-6 and resistin in single vessel disease group (r=0.190, p=0.112) was found, but higher positive correlation in two vessels disease group (r=0.240, p=0.323) and the highest positive correlation of interleukin-6 and resistin was found in three vessels disease group (r=0.324, p=0.221). Conclusion: The study showed that the resistin and interleukin plasma concentrations were significantly increased in 3VD which shows the role of these cytokines in ischemic heart disease. Key Words: Resistin, Interleukin 6, Ischemic Heart Disease